Challenges to National Cancer Institute–Supported Cooperative Group Clinical Trial Participation: An ASCO Survey of Cooperative Group Sites - Baer, Allison R. (American Society of Clinical Oncology, 2010)
Anecdotal information regarding clinical research sites limiting participation in NCI-funded cooperative group studies prompted ASCO to collect data on and investigate the reasons behind this trend.